Safe eradication of large established tumors using neovasculature‐targeted tumor necrosis factor‐based therapies. Issue 2 (8th January 2020) - Huyghe, Leander; Van Parys, Alexander; Cauwels, Anje; Van Lint, Sandra; De Munter, Stijn; Bultinck, Jennyfer; Zabeau, Lennart; Hostens, Jeroen; Goethals, An; Vanderroost, Nele; Verhee, Annick; Uzé, Gilles; et al.
Abstract: Systemic toxicities have severely limited the clinical application of tumor necrosis factor (TNF) as an anticancer agent. Activity‐on‐Target cytokines (AcTakines) are a novel class of immunocytokines with improved therapeutic index. A TNF‐based AcTakine targeted to CD13 enables selective activation of the tumor neovasculature without any detectable toxicity in vivo . Upregulation of adhesion markers supports enhanced T‐cell infiltration leading to control or elimination of solid tumors by, respectively, CAR T cells or a combination therapy with CD8‐targeted type I interferon AcTakine. Co‐treatment with a CD13‐targeted type II interferon AcTakine leads to very rapid destruction of the tumor neovasculature and complete regression of large, established tumors. As no tumor markers are needed, safe and efficacious elimination of a broad range of tumor types becomes feasible. Synopsis: TNF and IFN‐γ are cytokines with great anticancer potential but with limited clinical application due to side‐effects. In the present study, the tumor endothelium is identified as target cell for their antitumor activity and new biologics that allow their safe targeting are developed. By using transgenic mouse technologies the tumor endothelium was identified as target for the antitumor effect of TNF and IFN‐γ. TNF and IFN‐γ AcTakines were developed by fusing inactivated cytokine mutants to a CD13 single domain antibody (resp. CD13‐AFR and CD13‐AFN‐II), allowing selective targeting of cytokine activity to the tumor endothelium. CD13‐AFR synergized with immunotherapies (CD8‐AFN or CAR T‐cells) for immune‐mediated killing of solid tumors, without side‐effects. Combined treatment with CD13‐AFR and CD13‐AFN‐II resulted in selective apoptosis of the tumor endothelium and complete tumor destruction, without side‐effects. Abstract : TNF and IFN‐γ are cytokines with great anticancer potential but with limited clinical application due to side‐effects. In the present study, the tumor endothelium is identified as target cell for their antitumor activity and new biologics that allow their safe targeting are developed.